Design and analysis of a novel compact compliant actuator with variable impedance - Haoyong Yu; Sunan Huang; Gong Chen; Siew-Lok Toh; Cruz, M. S.; Ghorbel, Y.; Chi Zhu; Yuehong Yin (2012 IEEE International Conference on Robotics and Biomimetics, 2012)
Compliant Actuators are desirable for human friendly robotics, especially for assistive and rehabilitation robots that have direct physical interaction with human users. Various designs of Series Elastic Actuators (SEA) have been developed for these applications. This paper presents a novel SEA design with variable impedance for human-friendly robotics applications that overcomes the major limitations in the existing SEA designs. This novel design consists of a servomotor, a ball screw, a torsional spring between the motor and the ball screw, and a set of translational springs between the ball screw nut and the external load. The soft translational springs are used to handle the low force operation and reduce output impedance, stiction, and external shock load. The torsional spring, being in the high speed range, has high effective stiffness and improves the system bandwidth in large force operation when the translational springs are fully compressed. We first review the merits and the limitations of current series elastic actuators. We then explain the construction and the working principle of our new design, followed by the dynamic modeling and analysis of the actuator. We also show the preliminary testing results of a prototype actuator designed for a lower limb exoskeleton for gait rehabilitation.